Perbanyakan Bibit Stek Umbi dan Uji Adaptabilitas Plasma Nutfah Garut (Marantha arundinaceae L.) - nFN Sutoro; nFN Hadiatmi (Buletin Plasma Nutfah, 2011)
Multiplication of Propagated Tuber and Adaptability Test of Arrowroot Germplasm. Increasing arrowroot production needs technology production and variety suitable to the plant environment. Production constraints for arrowroot are seedling (stolon and tuber) limitation of cultivars adapted to the production area. Experiment had been carried out by using two factors (seedling source and variety) planted under randomized complete block design, three replications to study their germination capability. Three parts of seedlings source (tip, middle and basal part of tuber, 2 buds each) as first factor, and 10 varieties as second factor. Effect of seedling (stolon and tuber) of arrowroot and variety (10 accessions) were tested to study their adaptability had been done in 3 locations (Bogor, Cianjur and Serang). Seedling were planted at 50 cm x 40 cm, one row for each treatment. Tip-part and base-part of tuber showed better germination than middle-part of arrowroot tuber. There were effect of genotypic and environment interaction to tuber and starch yield. Accession No. 27 (Tasikmalaya), No. 28 (Gunung Kidul), No. 29 (Garut), No. 58 (Karawang), No. 387 (Banjarnegara), No. 403 (Banyumas), No. 478 (Brebes), dan No. 625 (Cilacap) could be categorized as stabil, while No. 626 (Cilacap) was more responsive while No. 627 (Malang) less responsive to environment changes. AbstrakPeningkatan produksi garut memerlukan teknik budi daya dan varietas yang sesuai dengan lingkungan tumbuh tanaman. Salah satu kendala dalam peningkatan produksi garut adalah sulitnya mendapatkan bibit dalam jumlah relatif banyak dan terbatasnya varietas yang cocok di daerah pengembangan. Percobaan telah dilakukan dengan menggunakan rancangan acak kelompok lengkap dengan perlakuan dua faktor, dengan tiga ulangan. Faktor pertama adalah stek umbi dengan dua mata tunas pada bagian ujung, tengah, dan pangkal. Faktor kedua adalah 10 aksesi garut. Penelitian bertujuan untuk mengetahui adaptabilitas 10 aksesi plasma nutfah garut, dilaksanakan di tiga lokasi, yaitu di Bogor, Pacet, dan Serang. Bibit ditanam dengan jarak 60 cm x 40 cm, satu baris tanaman tiap perlakuan. Hasil percobaan menunjukkan bahwa persentase stek umbi yang tumbuh pada bahan pangkal dan ujung lebih tinggi daripada stek umbi bagian tengah. Aksesi No. 27 (Tasikmalaya), No. 28 (Gunung Kidul), No. 29 (Garut), No. 58 (Karawang), No. 387 (Banjarnegara), No. 403 (Banyumas), No. 478 (Brebes), dan No. 625 (Cilacap) dapat dikategorikan stabil, sedangkan aksesi No. 626 (Cilacap) lebih responsif, dan aksesi No. 627 (Malang) kurang responsif terhadap perubahan lingkungan.